Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_367_374
|View full text |Cite
|
Sign up to set email alerts
|

Grain Selection during Solidification in Spiral Grain Selector

Abstract: A macro-scale ProCAST and a meso-scale Cellular Automaton Finite Element model (CAFE) are used to simulate the competitive growth and grain selection during solidification in spiral grain selector, which is widely used in industry to produce single crystal turbine blades. The macro-model ProCAST calculates the macroscopic heat transfer and fluid flow and the calculated thermal profiles are then used as input in the meso-scale CAFE model to predict grain structures and grain orientations. Competitive growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…This mechanism is widely used in the DS technique to produce the DS turbine blades and also contributes to the grain orientation control in the starter block of the grain selector for SX turbine blades. [18,[25][26][27] However, it is not capable of explaining the competitive growth that occurs within the spiral where there is the absence of an axial texture.…”
Section: Mechanism Of Grain Selection In Spiral Selectorsmentioning
confidence: 95%
“…This mechanism is widely used in the DS technique to produce the DS turbine blades and also contributes to the grain orientation control in the starter block of the grain selector for SX turbine blades. [18,[25][26][27] However, it is not capable of explaining the competitive growth that occurs within the spiral where there is the absence of an axial texture.…”
Section: Mechanism Of Grain Selection In Spiral Selectorsmentioning
confidence: 95%
“…[9,11] It has been shown that Ta is an important alloying addition to Fe-Al, as it can form the ternary Laves phase with the hexagonal C14 structure. [9] Recent investigations indicate that, in addition to the formation of the (Fe,Al) 2 Ta Laves phase, when Ta is added to Fe 3 Al, there is the unexpected formation of the Heusler-type phase. [12] It is not surprising, therefore, that the Fe-Al-Ta system has been studied with an emphasis on the Laves and Heusler phases, and on the relationship existing between alloy composition, phase stability, microstructure, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] However, with increasing demands on efficiency and step increase in turbine entry temperatures, there has been a keen interest in the development of alternative alloy systems. [3] One alternative that has been explored refers to the RM-Al-X system, where RM = Ta, Nb and X = Pd, Fe, Ti.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 19 shows the modeled three-dimensional (3D) grain structures and orientations in the starter block (39). Figure 19(a) is the predicted 3D grain structure in the grain selector including the starter block and the spiral.…”
Section: The Role Of Starter Blockmentioning
confidence: 99%